2018
DOI: 10.1080/17429145.2018.1499970
|View full text |Cite
|
Sign up to set email alerts
|

The specific responses to mechanical wound in leaves and roots of Catharanthus roseus seedlings by metabolomics

Abstract: The mechanical wound is one of the unavoidable threats to survival of plants. More researchers focus on the effect of mechanical wound to the over-ground tissues. And the effects of wound to roots were frequently ignored, although it is an important organ for plant growth. In our studies, the metabolomics study was performed to reveal the mechanical wound effects in Catharanthus roseus on roots and leaves by combining gas chromatography-mass spectrometer (GC-MS), liquid chromatograph-mass spectrometer (LC-MS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…In the present study, we found that GAL accumulation was significantly increased with increasing exposure time. Some of the studies had reported that wounding stress significantly increases the contents of benzylisoquinoline alkaloids, shikimic acid, primary or secondary metabolites [ 31 , 45 , 46 ]. Specifically, integrated transcriptomic and metabolomic analysis of benzylisoquinoline alkaloids in wounded Papaver somniferum revealed significant increases in the narcotine and papaverine accumulation [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we found that GAL accumulation was significantly increased with increasing exposure time. Some of the studies had reported that wounding stress significantly increases the contents of benzylisoquinoline alkaloids, shikimic acid, primary or secondary metabolites [ 31 , 45 , 46 ]. Specifically, integrated transcriptomic and metabolomic analysis of benzylisoquinoline alkaloids in wounded Papaver somniferum revealed significant increases in the narcotine and papaverine accumulation [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In carrot, wounding stress increased the production and accumulation of caffeoylquinic acids [ 29 , 30 ]. In a recent study, secondary metabolites in the mechanically wounded leaves and roots of Catharanthus roseus seedlings were analyzed [ 31 ]. However, metabolic profile of the C. roseus callus was not reported.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, terpenes and tannins and terpenoids are synthesized by the plant as a part of the defense system against herbivores [ 104 , 105 ]. The belowground part of the plant also induces the intensive production of secondary metabolites after wounding [ 106 ]. The whole plant synthesizes responsive secondary metabolites which can hinder the DNA extraction in the samples from intensively managed grasslands where the cutting and trampling was most severe.…”
Section: Discussionmentioning
confidence: 99%
“…Host plant metabolites play an important role in deterring or minimizing herbivory, and host metabolites have been shown to impact pest insect behavior and host preference in hemipteran pests [49,50,51]. Plant metabolites can be constitutive or induced [52], and can have diverse functions, including: Defense against herbivores or pathogens [53], as a response to mechanical damage [54,55], and as a response to environmental stress [56]. The leaf metabolites found in mandarin selections and pummelo provide additional data on the complex vector-host plant interactions of D. citri probing Citrus , but do not explain specific aspects of the observed probing differences.…”
Section: Discussionmentioning
confidence: 99%